Features of the pathomorphological structure of the aterosclerotic plaques of carotid aterosclerosis - Yu. I. Kuzyk (Patologìâ)
Carotid arteriosclerosis is a recognized leader among causes of ischemic disorders of the cerebral circulation. It is known that brain infarction occurs with atherosclerotic stenosis and thrombosis of the carotid arteries in approximately 40 % of cases. The peculiar geometry of carotid bifurcation creates conditions for the development of atherosclerotic plaques.